Renewable Energy Development in China : A 40-Year China-World Bank Partnership - De Gouvello, Christophe (World Bank, Washington, DC, 2021)
China’s remarkable economic growth required dramatic growth of energy consumption and continuous changes in the nation’s energy economy. The World Bank supported the efforts of the Chinese government to develop and revitalize the country’s energy sector to meet the daunting challenges it faced while continuously warning that the unrestrained reliance on coal would lead to unsustainable stress on the local and global environment. In mid-1980s, the Chinese government and the World Bank embarked on a long and arduous journey to develop renewable energy (RE) to lessen the impacts on the environment and avoid excessive reliance on coal to alleviate the debilitating power shortages that constrained the economy. This paper focuses on the more than 40-year partnership with the World Bank along China’s long journey to develop a large-scale, efficient, and competitive RE industry in the country and globally. While the projects supported by the World Bank and their role are highlighted in this paper, this support should only be seen as a catalyst. The remarkable development of renewable energy in China was primarily guided by the multiple Chinese authorities at the national, provincial, and county levels, implemented by the many public and private companies, and fueled by local financing institutions. The paper is structured along the four stages of RE development in China, which are detailed in a companion report. It highlights the key milestones of this partnership, its achievements, and challenges, detailing World Bank support and main activities that contributed to China’s rise from a lagger to a leader.